Faktor–Faktor yang Mempengaruhi Investment Decision Making serta Dampaknya Terhadap Financial Wellbeing Pada Generasi Muda di Kota Jambi - Dhiya Ulhaq; Wirmie Eka Putra; Misni Erwati (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2025)
This study was conducted to determine the factors that influence Investment Decision Making and its impact on Financial Wellbeing of the younger generation in Jambi City. This study is a type of quantitative research. The determination of the number of samples in this study was 399 respondents with the sampling technique used was purposive sampling. The data used is primary data obtained through a digital questionnaire, namely a google form with a Likert scale. The data analysis method in this study uses PLS (Partial Least Square) using Smart PLS 4 software. The results of this study indicate that Financial Literacy, Mental Budgeting, Self Control and Financial Behavior have a significant positive effect on Investment Decision Making and Financial Behavior. Then Investment Decision Making plays an important mediator in the relationship between these variables. Therefore, understanding and awareness of these factors are important to increase success in investing. This study was limited to respondents from the younger generation in Jambi City, with data coverage still being suboptimal. Therefore, it is recommended that further research expand the population reach to obtain more representative data.